Isotopic resonance at 370 ppm deuterium negatively affects kinetics of luciferin oxidation by luciferase. Issue 1 (December 2018) - Rodin, Sergey; Rebellato, Paola; Lundin, Arne; Zubarev, Roman
Abstract Since 1930s, it has been known that some biochemical and biological processes exhibit abnormal kinetics at a deuterium concentration in the local environment of 250–600 ppm, which is 2–4 times higher that the normal concentration of 150 ppm D. We sought to test if the kinetics of firefly luciferase oxidizing luciferin, the reaction widely used as a read-out in various biochemical assays, is also affected by an elevated deuterium content. To this end, both luciferase and luciferin substrate solutions were prepared based on water with extra deuterium added to a concentration ranging from 150 ppm and up to 10, 000 ppm (1%). Upon mixing the solutions, the luminescence intensity at different times was compared with that of the corresponding control solutions with 150 ppm D. A broad negative resonance was detected (p < 10−6 ), with a ≈20% drop in luminescence at 370 ppm D. Given that, on average, about half of hydrogen atoms in proteins are not exchangeable in solution, this value corresponds to ≈260 ppm of deuterium in all enzyme's hydrogens, in a very good agreement with the prediction of the Isotopic resonance hypothesis.